Analisis Faktor Penentu Minat Berwirausaha Pada Santri Pondok Pesantren Anwarul Huda - Mohamad Bastomi; Dwiyani Sudaryanti (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The government is working to attract entrepreneurs to help strengthen Indonesia's economic structure. The community's low interest in becoming an entrepreneur is an important issue that needs to be addressed. This research is used to analyze several factors that influence interest in entrepreneurship. Quantitative descriptive analysis was used to collect data through a questionnaire survey. Random samples were taken from the students of the Anwarul Huda Islamic boarding school. Several linear regression tests were used to analyze the data processed with the SPSS 25 application and the entrepreneurial interest of students. This research description explains that all independent variables have a significant effect on the dependent variable. Interest in entrepreneurship is determined by the biggest factors in the form of self-efficacy, followed by locus of control, adversity intelligence, spiritual motivation and the smallest is religiosity. The results of this study can be used as a reference for institutions in an effort to increase interest in entrepreneurship through the preparation of various programs related to the activities of students in Islamic boarding schools.